Frequency of New Onset Diabetes Mellitus in Patients Receiving Treatment for Diffuse Large B Cell Lymphoma - Younas, Aqsa; Arshad, Ayaz; Arslan, Muhammad (Indus Journal of Bioscience Research, 2025)
Objectives: To determine the frequency of new-onset diabetes mellitus in patients receiving treatment for diffuse large B-cell lymphoma. Methodology: This study was done at Shaukat Khanum Memorial Cancer Hospital & Research Center, Lahore after Six months following approval of the study synopsis from 7th February to 7th May. We enrolled 150 patients aged 18–40 years with newly diagnosed DLBCL were enrolled using non-probability consecutive sampling. Patients with prior diabetes or central nervous system lymphoma were excluded. Glycemic status was assessed post-chemotherapy using fasting blood glucose and HbA1c. Associations with demographic and clinical variables were analyzed. Results: New-onset diabetes mellitus was observed in 32.0% (n = 48) of patients. A significant association was found with family history of diabetes (p = 0.009) whereas age, BMI, gender, smoking, alcohol use, lymphoma stage, or type of therapy had no significant association. Conclusion: The frequency of new-onset diabetes among DLBCL patients undergoing chemotherapy is substantial. Family history of diabetes emerged as a significant risk factor. Routine screening for hyperglycemia should be incorporated into oncology care to ensure early diagnosis and management of diabetes during cancer treatment.